Composition and distribution of zooplankton across an upwelling front on the northern Portuguese coast during summer - Queiroga, Henrique
Zooplankton was sampled during the summer of 1995 from a grid of 34 shelf stations located off the Ria de Aveiro (northwestern Portugal), which were arranged into cross-shore transects extending either to the shelf break or to the 50 m isobath. At each station, a bongo net was hauled obliquely from close to the bottom or a maximum depth of 50 m to the surface. STD casts were made also at each station and wind data were obtained from a land station. Analysis of salinity and temperature data detected the presence of strong thermohaline stratification and a lens of reduced salinity water at the surface. A well-defined front, located at a depth of 10 to 35 m, separated cold water close to shore from warmer offshore water. Isopycnals between the front and the shore were bent towards the surface. The structure of the thermo- haline features was consistent with the upwelling-favourable winds measured during the sampling period. A classification and a multivariate analysis of variance of the more abundant species showed the presence of two distinct assemblages that were separated by the front, indicating that these formations are important features structuring the zooplanktonic community of upwelling areas. The data further indicate that the zooplankton was composed of Palaeartic Atlantic and Mediterranean neritic species, and that oceanic species were absent from the samples. The absence of oceanic species is interpreted as resulting from the offshore displacement of the slope poleward flow and of the Portugal Current that takes place during the summer, as a response to upwelling-favourable winds.